1994
DOI: 10.1023/a:1018974818012
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A variable long path gas cell was used to measure the sorption of organic vapors by a polymer slab. Unfilled polydimethylsiloxane (PDMS) slabs were cast and used to study the sorption of a series of aliphatic alcohols. The PDMS slab was suspended in the gas cell and exposed to low relative pressures of an alcohol vapor. The sorption rate of the alcohol vapor by the PDMS slab was obtained by measuring the decrease in the amount of free diffusant in the gas cell. The diffusion coefficients of the alcohols in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…8 The values of the diffusion coefficients obtained from these techniques agree well with previously reported values. Wurster, Buraphacheep, and Patel 2 used a horizontal attenuated total reflectance (H-ATR) cell to determine diffusion coefficients of neat liquids in semisolids.…”
Section: Introductionsupporting
confidence: 90%
“…8 The values of the diffusion coefficients obtained from these techniques agree well with previously reported values. Wurster, Buraphacheep, and Patel 2 used a horizontal attenuated total reflectance (H-ATR) cell to determine diffusion coefficients of neat liquids in semisolids.…”
Section: Introductionsupporting
confidence: 90%
“…In Table 2 our results for the diffusion coefficient are given and compared with the data from the literature with which we find good agreement for ethanol and some deviation for 1-butanol. We note that the cross-linking (curing) of PDMS during preparation of the stamp does not necessarily lead to one and the same material in the different preparations and do not consider it meaningful to further analyze the differences of diffusion coefficients between this study and previous studies, [2][3][4][5]7 as the PDMS preparation is either different from our method or no information on the preparation method is available.…”
Section: ∂F S ∂Tmentioning
confidence: 94%
“…We are interested in the average mass flux through the channel walls into the PDMS. According to the 1-D diffusion assumption (3), this should follow a t -1/2 behavior. In Figure 2 the numerically calculated average nondimensional mass flux, m′* ) -Dt s /w 2 ∂F s /∂x* is plotted as a function of (t*) -1/2 for Dt s /w 2 ) 0.2.…”
Section: U(t)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al reported diffusion constants of 1.4 × 10 -5 to 2.2 × 10 -5 cm 2 /s for oxygen diffusion in silica-filled and unfilled PDMS films at room temperature . Buraphacheep et al measured slightly smaller diffusion constants for various alcohols . For the case of PDMS elastomers created from the Sylgard 184 kit, it is important to note that the starting material may contain oligomers with terminal Si−H and Si−CC groups that can possibly react with bromine in the illuminated samples.…”
Section: Fabrication Of Bz Microchipsmentioning
confidence: 99%